Supply Chain Practices of Lean Healthcare Performance Improvement (LHPI) in Malaysian Healthcare Industry - Habidin, Nurul Fadly; Hudin, Norlaile Salleh; Wan Mustaffa, Wan Salmuni; Anuar, Azyyati; Mohd Fuzi, Nursyazwani; Bakri, Mohammed Hariri; Ong, Sharon Yong Yee (International Journal of Supply Chain Management, 2020)
The purpose of this study is to review the supply chain factors of lean healthcare performance improvement (LHPI). Seven supply chain factors of LHPI (leadership, employee engagement, customer engagement, continuous improvement, just in time, lean production, and workflow processes) had been identified. The researcher chose Malaysia’s healthcare industry as a population of this study because the industry will face strong pressures and take initiatives in order to manage the healthcare in a cost and performances effective manner. For practical implications, the LHPI tool process is user friendly, easy to use, systematic and practical thus can assist practitioners to understand the concept of lean healthcare practices in the Malaysian healthcare industry. Thus, the implementation of LHPI is significant to the Malaysian healthcare industry in order to improve the supply chain factors.